COMPARATIVE ANALYSIS OF PUNJABI LANGUAGE VARIATIONS; A STUDY OF LEXICAL AND SYNTACTIC DIFFERENCES BETWEEN INDIA AND PAKISTAN - Umar Farooq Akram; Dr Aftab Akram (International Journal of Contemporary Issues in Social Sciences, 2024)
This study aims to contrast the vocabulary and syntax of Punjabi in India and Pakistan, elucidating the linguistic variations between the two regions. It explores the discrepancies in vocabulary and sentence structure within ostensibly identical languages. Research is conducted to discern the similarities and differences between these languages, investigating the extent of their lexical and syntactic convergence or divergence and their impacts on the users. In this qualitative research endeavor, a case study methodology was employed to manually collect data, supplemented by interviews. The paper delves into historical factors, including language interactions and sociolinguistic influences, which may have shaped the identified syntactic patterns. Furthermore, this research scrutinizes the implications arising from these syntactic distinctions. Various linguistic elements, such as case markers, verb conjugations, and agreement patterns, are meticulously analyzed to delineate disparities and parallels between the two language variants. The study reveals lexico-syntactic similarities and distinctions between Pakistani and Indian Punjabi, highlighting pronunciation nuances leading to differing meanings for similarly spelled words.